Adsorption of antibiotic, heavy metal and antibiotic plasmid by a wet-state silicon-rich biochar/ferrihydrite composite to inhibit antibiotic resistance gene proliferation/transformation. (May 2023) - Chen, Zaiming; Shen, Jiahao; Xu, Xiaoqin; Feng, Huajun; Wang, Meizhen
Abstract: Decreasing bioaccessible antibiotics, heavy metals, and antibiotic resistance genes (ARGs) in soil by adsorption is an attractive, but unrealized, approach for ARG risk reduction. This approach has the potential to reduce the (co)selection pressure from antibiotics and heavy metals on bacteria and ARG horizontal gene transformation to pathogens. Here, a wet-state silicon-rich biochar/ferrihydrite composite (SiC–Fe(W)) synthesized by loading ferrihydrite onto rice straw-derived biochar was examined for i) adsorption of oxytetracycline and Cu 2+ to reduce (co)selection pressure and ii) adsorption of extracellular antibiotic resistance plasmid pBR322 (containing tet A and bla TEM-1 ) to inhibit ARG transformation. SiC–Fe(W) gained the adsorption priority of biochar (for Cu 2+ ) and wet-state ferrihydrite (for oxytetracycline and pBR322) and showed adsorptive enhancement (for Cu 2+ and oxytetracycline) from a more wrinkled and exposed surface from biochar silica-dispersed ferrihydrite and a more negatively charged biochar, and the adsorption capacity for SiC–Fe(W) was 17–135 times that of soil. Correspondingly, 10 g/kg SiC–Fe(W) amendment increased the soil adsorption coefficient K d by 31%–1417% and reduced the selection pressure from dissolved oxytetracycline, co-selection pressure from dissolved Cu 2+, and transformation frequency of pBR322 (assessed with Escherichia coli ). The development of Fe–O–Si bonds on silicon-rich biochar in alkaline enhanced ferrihydrite stability and adsorption capacity (for oxytetracycline), presenting a new potential strategy of biochar/ferrihydrite composite synthesis for adsorptive inhibition of ARG proliferation and transformation in ARG pollution control. Graphical abstract: Image 1 Highlights: SiC–Fe(W) containing silica-stabilized and high-surface ferrihydrite and sichar was synthesized. SiC–Fe(W) held adsorption capacity exceeding biochar and wet-state ferrihydrite for Cu 2+ and oxytetracycline. Adsorptive inhibition of ARG proliferation and transmission in soil was realized by SiC–Fe(W). SiC–Fe(W) promoted the persistence of soil sorption enhancement towards oxytetracycline and ARG in dry-wet cycle.